2022
DOI: 10.1186/s13098-022-00840-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between central obesity and bone mineral density: a Mendelian randomization study

Abstract: Background The relationship between obesity and osteoporosis is an important public health issue. The goal of this study was to investigate whether and to what extent central obesity traits affect bone mineral density (BMD). Methods We conducted a two-sample Mendelian randomization analysis. Genomewide significant single nucleotide polymorphisms associated with waist circumference, hip circumference, waist-to-hip ratio, waist circumference adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…In terms of overall obesity, we found that BMI, a measurement of overall obesity, was causally and positively associated with BMD, and the genetic determination of BMI is different but similar across different skeletons ( 27 ). In terms of central obesity, our study suggested variations in the ability of different central obesity traits to influence BMD and found that hip circumference adjusted by BMI (negatively) and waist-to-hip ratio (positively) may be important factors causally influencing BMD ( 28 ). Recent studies have demonstrated that sarcopenic obesity is associated with an increased risk of physical disability, osteoporosis and nonvertebral fractures in older adults when compared to those with obesity ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 82%
“…In terms of overall obesity, we found that BMI, a measurement of overall obesity, was causally and positively associated with BMD, and the genetic determination of BMI is different but similar across different skeletons ( 27 ). In terms of central obesity, our study suggested variations in the ability of different central obesity traits to influence BMD and found that hip circumference adjusted by BMI (negatively) and waist-to-hip ratio (positively) may be important factors causally influencing BMD ( 28 ). Recent studies have demonstrated that sarcopenic obesity is associated with an increased risk of physical disability, osteoporosis and nonvertebral fractures in older adults when compared to those with obesity ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 82%
“…Afterward, we extracted the SNPs and their corresponding statistical data that were associated with the outcome. We selected 15,14,14,19,18,20,20, and 20 SNPs as instrumental variables for the causal analyses between breakfast skipping and FABMD, FNBMD, LSBMD, TBBMD (0-15 years), TBBMD (15-30 years), TBBMD (30-45 years), TBBMD (45-60 years), and TBBMD (over 60 years). Detailed information is provided in Additional file 2.…”
Section: Eligible Snpsmentioning
confidence: 99%
“…Its mechanism is similar to that of randomised controlled trials (14,15), making this geneticvariable-based analytical method capable of yielding more reliable conclusions (16). Previous MR studies have demonstrated causal effects of factors such as fasting glucose (17), low-density lipoprotein cholesterol (18), and central obesity (19) on the development of BMD. However, an MR study on the causal effect of breakfast skipping on BMD has not been conducted.…”
Section: Introductionmentioning
confidence: 97%
“…Also, concordant and consistent findings emanating from MR analyses using multiple anthropometric markers of central-and general-obesity could strengthen the evidence pertaining to their putative causal roles in ensuing PCOS. Anthropometric traits are customarily exploited in MR studies as valid and reliable surrogate markers for operationalizing central-and general obesity [30][31][32]. In these studies, multiple anthropometric markers were incorporated in univariable MR to gain evidence on causal roles of central-and general obesity [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric traits are customarily exploited in MR studies as valid and reliable surrogate markers for operationalizing central-and general obesity [30][31][32]. In these studies, multiple anthropometric markers were incorporated in univariable MR to gain evidence on causal roles of central-and general obesity [30][31][32].…”
Section: Introductionmentioning
confidence: 99%